1995
DOI: 10.3758/bf03208369
|View full text |Cite
|
Sign up to set email alerts
|

Facial identity and facial speech processing: Familiar faces and voices in the McGurk effect

Abstract: An experiment was conducted to investigate the claims made by Bruce and Young (1986) for the independence of facial identity and facial speech processing. A well-reported phenomenon in audiovisual speech perception-the McGurk effect (McGurk & MacDonald, 1976), in which synchronous but conflicting auditory and visual phonetic information is presented to subjects-was utilized as a dynamic facial speech processing task. An element of facial identity processing was introduced into this task by manipulating the fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
111
2
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(132 citation statements)
references
References 28 publications
16
111
2
3
Order By: Relevance
“…Walker, Bruce, and O'Malley (1995) have reported that the familiarity of faces modulated the degree to which visual information influenced speech perception in the audiovisual "McGurk" illusion (McGurk & MacDonald, 1976). have corroborated an influence of face familiarity on speech reading for static photographs of faces; subjects were found to be more efficient in speech reading for personally familiar faces.…”
mentioning
confidence: 54%
“…Walker, Bruce, and O'Malley (1995) have reported that the familiarity of faces modulated the degree to which visual information influenced speech perception in the audiovisual "McGurk" illusion (McGurk & MacDonald, 1976). have corroborated an influence of face familiarity on speech reading for static photographs of faces; subjects were found to be more efficient in speech reading for personally familiar faces.…”
mentioning
confidence: 54%
“…Familiarity, and thus identity, can also affect how audiovisual speech is processed. A familiar face matched with an unfamiliar voice is less effective at eliciting the McGurk effect than an unfamiliar face paired with an unfamiliar voice (Walker, Bruce & O'Malley, 1995), suggesting that facial identity and vocal identity are not processed completely independently of one another. A person's facial identity and vocal identity during speech share the same general dynamic temporal patterns.…”
Section: Discussionmentioning
confidence: 93%
“…Other research shows that remembered attributes of a visual talker interact with lexical and indexical memory (Sheffert & Fowler, 1995). Familiarity with a talker's face has also been shown to improve the accuracy of visual phoneme identification (Schweinberger & Soukup, 1998), of short-term memory for audiovisual words, and of audiovisual speech integration (Walker, Bruce, & O'Malley, 1995).…”
Section: Interactions Between Indexical and Linguistic Processing Acrmentioning
confidence: 99%